STUDI HISTOPATOLOGI GONAD GASTROPODA LAUT (THAIS TUBEROSA DAN MONODONTA LABIO) YANG MENGALAMI IMPOSEKS AKIBAT TERPAPAR TRIBUTYLTIN (TBT) - Noor, Sri Yuningsih (Torani Journal of Fisheries and Marine Science, 2015)
Tributyltin (TBT) is an organotin compound used as antifouling material for ship or boat paints to preventattachment of marine biota on the wall of ships or boats. The most dangerous effect of TBT bioaccumulation onmarine organisms, particularly gastropods, is the failure on the reproduction system, such as the occurrence ofimposex symptoms. The main purposes of this study are to know the histopathology of gonads by species Thaistuberosa and Monodonta labio that has been exposed to imposeks the compound tributyltin (TBT). The samplingof Thais tuberosa and Monodonta labio was conducted at 2 sites: Manado Port and Tateli Coastal Waters. Thehistopathology test was conducted in the Central Diagnostic Laboratory of Anatomic Pathology, Manado, withHaematoxylin-Eosin (HE) technique. The result showed that histopatology gonads marine gastropods type Thaistuberosa and Monodonta labio there has been a change in the tissues showing the imposex character, ifcompared with tissues of normal individuals of male and female, but in these changes tissues not cause damagecaused by a compound tributyltin (TBT).Keywords : Histopatology of gonad, Gastropods, Imposex, Tributyltin